Questioning to stimulate learning and thinking featuring the quilt model (Utah : Linton Professional Development Corporation, 1999)
Part 1: stage 1 ; Part 2: stages 2 & 3 ; Part 3: stages 4 & 5
volume 1. Elementary edition - volume 2. Secondary edition
Presenter: Jackie Walsh and Beth Sattes
Keywords: Constructivism (Education); Thought and thinking -- Study and teaching